Strategies for Enhancing Resilience in Horticultural Crops Against Combined Abiotic Stresses - Padilla, Yaiza; Fotopoulos, Vasileios; Ntatsi, Georgia; Calatayud, Ángeles; Penella, Consuelo; Sabatino, Leo; Mozafarian, Maryam (My University, 2025)
Horticultural crops are increasingly exposed to simultaneous abiotic stresses such as drought, salinity, and temperature extremes, which often exacerbate each other's effects, leading to severe yield and quality losses. Addressing these multifaceted challenges necessitates the development and application of integrated and innovative strategies. This review highlights recent advancements in methodologies to enhance the resilience of horticultural crops against combined abiotic stresses. Key approaches include breeding and selection of stress-tolerant cultivars, grafting onto stress-tolerant rootstocks, and priming strategies such as the application of nanoparticles and biostimulants, which have shown promise in modulating physiological and biochemical responses under stress conditions. These techniques collectively improve plant water status, enhance nutrient uptake efficiency, and upregulate antioxidant enzymatic activities, thereby mitigating oxidative damage and sustaining plant growth and productivity. By integrating these strategies, it is possible to optimize the physiological resilience and biochemical robustness of horticultural crops, ensuring stable yields and quality under increasingly challenging environmental conditions. These findings provide actionable insights into sustainable crop management and contribute to global efforts to enhance food security in the face of climate variability.
Keywords: biostimulants; climate change; combined stress; grafting; nanotechnology; plant breeding